Mining and characterization of oxidative stress‐related binding proteins of parthenolide in Xanthomonas oryzae pv. oryzae. Issue 8 (20th May 2022) - Zhou, Qian; Li, Linwei; Liu, Fei; Hu, Jun; Cao, Yan; Qiao, Siwei; Zhou, Yuxin; Wang, Bi; Jia, Yihe; Chen, Yu; Xu, Shu; Feng, Xu
Abstract: BACKGROUND: Lack of control agents and development of bacterial resistance are emergent problems in the chemical control of rice bacterial blight, therefore novel bactericides against Xanthomonas oryzae pv. oryzae ( Xoo, the causal agent of rice bacterial blight) are urgently needed. We previously found that parthenolide (PTL) is a potential lead against Xoo, and PTL inhibits Xoo growth via oxidative stress. However, the mechanism of action of PTL against Xoo needs further elucidation. RESULTS: In this study, a biotinylated PTL probe was synthesized, and two important subunits in the respiratory chain (NuoF of complex I and SdhB of complex II) of Xoo were captured with the probe and identified with liquid chromatography tandem mass spectrometry (LC–MS/MS). The binding between them was verified with pull‐down and drug affinity responsive target stability technologies. In addition, purified proteins of NuoF and SdhB greatly lowered the antibacterial activity of PTL, and PTL evidently inhibited the enzyme activities of complexes I and II. Moreover, knockout of nuoF and sdhB in Xoo caused elevated reactive oxygen species (ROS) levels and increased sensitivity to PTL. Furthermore, molecular simulations indicated that PTL may form covalent bonds with Cys105 and Cys187 in NuoF and Cys106 in SdhB. CONCLUSION: PTL can directly bind to NuoF and SdhB, which impairs the enzyme functions of complexes I and II in the respiratory chain, leading to ROS accumulation in Xoo . This study will provide deep insight into the mechanism of action of PTL against Xoo . © 2022 Society of Chemical Industry. Abstract : Parthenolide can bind to NuoF and SdhB and react with GSH, which causes dysfunction of complexes I and II and reduction of ROS scavenging ability, leading to ROS accumulation.